After globalization - Cazdyn, Eric M.; Szeman, Imre, 1968- (Malden, Mass. : Blackwell Pub., 2011)
"Relentlessly, remorselessly, endlessly, we are told there is no alternative to globalization, whether our lecturers are bourgeois economists, progressive journalists, or imaginative litterateurs. Eric Cazdyn and Imre Szeman dare to go beyond the standard thinking of the day and query the very heart of mobile capital and its impact on daily life. Their alternative vision breathes new life into our sense of evolution and inevitability." Toby Miller, author of Globalization and Sport and -Global Hollywood "Cazdyn and Szeman begin the with the idea that the current economic crisis has historicized globalization, turning it from a process that looked as inevitable as, say, global warming still does, into an episode in the history of capitalism: hence the possibility not just of more globalization but of an 'after globalization.' And hence also, they argue, the renewed possibility of an 'after capitalism.' In powerful critiques of what they describe as the common sense of capital today they sketch out the terms in which changes more radical than substituting generous and honest leaders for the greedy and dishonest ones we've currently got might begin to be imagined." -Walter Benn Michaels, University of Illinois at Chicago.
Front Matter -- A Přcis: The Argument -- Part I: The Afterlife of Globalization -- Part II: The Limits of Liberalism -- Part III: The Global Generation -- Conclusion: Oh, don't ask why! -- Index.
Includes bibliographical references and index.
Print version record.
Keywords: Globalization in literature; Globalization; POLITICAL SCIENCE -- Globalization; Globalization; Globalization in literature; Internationalisatie; Electronic books